Police Research for the Indonesian National Police Cadets - Ari Setyawan, Nugroho (Proceedings of Police Academy, 2024)
This paper aims to explain police research. The study for this paper is conducted through a narrative literature review. The study finds that police research is a new field. The research is initially critical but later enriched with an evidence-based view. Police research is challenging because of the difficulty of the researchers collaborating with the police and translating research into practice. There are some steps (for a police researcher) to conduct research in policing successfully. The police cadets are inside researchers. They may have less difficulty entering the police organisation. Some points are suggested for the police cadets to be potential practitioner-academics (pracademic) in improving policing.